Aspekty etyczne systemów oceniania pracowników w instytucjach publicznych - Walenia, Alina (Annales. Etyka w Życiu Gospodarczym, 2015)
A performance appraisal system forms an integral part of any developed management concept. The efficiency of such an appraisal system is fostered in institutions which prioritise quality and continuous improvement, and where innovationfriendly actions are joined by those that build confidence. An efficient appraisal system is characterised as follows: it is systemic in character, regular, universal, flexible, concrete, transparent and simple in application. When implementing a modern appraisal system, care should be taken to adhere to ethically sound principles such as fairness, objectivity, goodness and truthfulness.